Transformasi Digital dan Implikasinya terhadap Produktivitas Tenaga Kerja di Sektor Jasa - Anjas Pratama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
The digital transformation has become a fundamental driver of change across all economic sectors, particularly in the service sector, which relies heavily on human capital and information technology. This study aims to explore the implications of digital transformation on labor productivity in the service sector in Indonesia. A mixed-method approach was employed, combining quantitative analysis of secondary productivity data from BPS (2015–2023) with qualitative interviews of 20 professionals across finance, health, and education sectors. The findings reveal a positive correlation between the adoption of digital technologies—such as cloud computing, digital workflow systems, and AI tools—and labor productivity, although the benefits vary across subsectors. However, the study also highlights challenges, including skills mismatches and uneven digital infrastructure. The results suggest that while digital transformation can significantly enhance productivity, it must be supported by continuous workforce upskilling and inclusive policy frameworks. The study contributes to the literature by providing sector-specific insights into the digital transition and offering recommendations for improving labor efficiency through strategic digital adoption.